Autophagy-Based Diagnosis of Pregnancy Hypertension and Pre-Eclampsia - Sharma, Surendra (Am J Pathol, 2018)
This commentary highlights the article by Aoki et al that shows that Atg7 deficiency–mediated placental autophagy imbalance may contribute towards pre-eclampsia.